Comparison Analysis of Engine Performance Using VVT-i System And Engine Without VVT-i System - Fikri, Ali (2011)
Nowadays, many demands from consumers to have a car with powerful engine and low of gasoline so vehicle manufactures think how to make engine like that. Vehicle manufactures develop technology which can increase of performance and the engine can have a great power and torque. Variable Valve Timing (VVT) can be used to problem solve above because variable valve timing can control timing valve. VVT can increase engine performance that can make the gasoline engine will increase power and torque. Research target that is to kwon influence variable valve timing to engine performance at four stroke engine 1298cc. Research uses four stroke engine with two types of engine use VVT-i and engine without using VVT-i. Two types of four stroke engine will testing above engine dynamometer. Calculation is conducted after got data of testing result. Base testing and analysis can be concluded that engine use VVT-i have higher performance than engine without VVT-i. From dynamometer test was get maximum torque from engine use VVT-i is 138.6 N.m at 4500rpm and maximum torque from conventional engine is 124.6 N.m at 4500 rpm. Maximum torque from engine use VVT-i is 107.3 BHP at 6000rpm and maximum torque from conventional engine is 94.5 BHP at 6000rpm.VVT-i organizes timing of valve which can make overlapping on the machine. Overlapping make number of air-fuel mixture in combustion chamber will increase which can make performance will increases.